Enantio‐ and Diastereoswitchable C−H Arylation of Methylene Groups in Cycloalkanes. Issue 36 (27th May 2019) - Andrä, Michal S.; Schifferer, Lukas; Pollok, Corina H.; Merten, Christian; Gooßen, Lukas J.; Yu, Jin‐Quan
Abstract: A complementary set of chiral N, N‐ligands enables the Pd‐catalyzed β‐C−H arylation of unbiased internal methylene groups in good yield and with high levels of enantio‐ and diastereoinduction. Both the dia‐ and enantioselectivity can be reversed, thus allowing the selective arylation of any of the four β‐C−H bonds in cycloalkanecarboxamides of various ring sizes. The method is applicable to a broad range of aryl iodides with electron‐withdrawing and ‐donating substituents in the o ‐, m ‐, or p ‐position. Abstract : Stereodivergent functionalization : An unprecedentedly selective β‐C−H arylation of directing‐group‐substituted cycloalkanes is reported. Known acetyl‐protected aminoethyl quinoline (APAQ) ligands give cis products with high yields, enantio‐ and diastereoselectivities. New ligands reversed the diastereoselectivity in favor of the trans products.